Humor and Hunger Affect the Response Toward Food Cues - Froehlich, Eva; Samaan, Larissa; Matsuzaki, Rie; Park, Soyoung Q (Frontiers in Psychology, 2021)
The omnipresence of food cues in everyday life has been linked to troubled eating behavior and rising rates of obesity. While extended research has been conducted on the effects of negative emotions and stress on food consumption, very little is known about how positive emotions affect eating and particularly attention towards food cues. In the present study, we investigated whether humor impacts attentional bias towards food and whether it will affect preferences for healthy and unhealthy food items, depending on the hunger state. To do so, a group of randomly assigned participants watched funny video clips (humor group, N = 46) or neutral ones (control group, N = 49). Afterwards, they performed a modified Posner cueing task with low or high caloric food images serving as cues. We found a significant group x hunger interaction. Compared to the control group, the humor group responded more slowly to food cues when hungry, whereas the opposite was true when participants were satiated. Additionally, our results suggest that hunger possibly directs attention away from healthy food cues and towards unhealthy ones. No group differences were found with respect to food preferences and regarding engagement and disengagement of attention. We discuss the potential of humor in counteracting aversive consequences of hunger on attention allocation towards food. We propose an underlying mechanism involving a combined reduction in cortisol levels and a decrease in activation of the reward system. However, given the novelty of the findings, further research is warranted, both to replicate the results as well as to investigate the suggested underlying processes.